Structure and Performance: Global Interdependence of Stock Markets around the Crash of October 1987. - Bertero, E; Mayer, C (1990)
Using a new data source on share price indices, this paper finds no evidence that the substantial variations in the reactions to the crash of October 1987 across countries are related to the structure of markets. However, trading halts and capital controls on residents may have moderated the speed of declines in some markets. The paper also examines one measure of interlinkages between markets, the trading of foreign stocks on domestic markets, and finds this to be closely related to interdependence between markets.